The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1136/jmedgenet-2019-106095
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of normal patterns of FOXF1 expression in a lethal disorder of lung development

Abstract: BackgroundAlveolar capillary dysplasia with misalignment of the pulmonary veins (ACDMPV) is a lethal disorder of lung development. ACDMPV is associated with haploinsufficiency of the transcription factor FOXF1, which plays an important role in the development of the lung and intestine. CNVs upstream of the FOXF1 gene have also been associated with an ACDMPV phenotype, but mechanism(s) by which these deletions disrupt lung development are not well understood. The objective of our study is to gain insights into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Rawlins EL 38 found that FOXJ1 is progressively expressed in ciliated cells during lung development and that when FOXJ1 is fully expressed in ciliated cell precursors, the cells stop proliferating or have a significantly longer division cycle. Differential expression analysis in this group of samples revealed high FOXJ1 expression ( P = 0.00024), and GO functional enrichment analysis suggested that FOXJ1 is involved in various aspects of respiratory differentiation, respiratory epithelial cells, ciliary cell differentiation, cilia assembly and motility 39 .…”
Section: Discussionmentioning
confidence: 80%
“…Rawlins EL 38 found that FOXJ1 is progressively expressed in ciliated cells during lung development and that when FOXJ1 is fully expressed in ciliated cell precursors, the cells stop proliferating or have a significantly longer division cycle. Differential expression analysis in this group of samples revealed high FOXJ1 expression ( P = 0.00024), and GO functional enrichment analysis suggested that FOXJ1 is involved in various aspects of respiratory differentiation, respiratory epithelial cells, ciliary cell differentiation, cilia assembly and motility 39 .…”
Section: Discussionmentioning
confidence: 80%
“…However, lung tissue contains a heterogeneous cell population and thus, the DMRs identified are not cell type specific. In human and mice lung tissue, FOXF1 is mainly expressed in mesenchymal, smooth muscle and endothelial cells [47,[49][50][51]. To study whether aberrant methylation of the FOXF1 locus is specific for one of these cell types, it would be interesting to study DNA methylation patterns in sorted cells from fresh ACD/MPV lung tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, this seems not to be the case, since genomic annotations of H3K27ac obtained by EPAT-ChIP were found to overlap with those produced by other research groups (e.g., ChIP-seq from ENCODE) [24]. To date, PAT-ChIP has been applied by different research groups to locus-specific and genome-wide studies, supporting the reproducibility of the entire procedure [31][32][33][34][35][36][37][38][39][40][41][42][43]. Notably, the last 2 years have seen the birth of three other procedures.…”
Section: The Development Of Ffpe-chip Techniques Over Timementioning
confidence: 94%